NP-hardness results for partitioning graphs into disjoint cliques and a triangle-free subgraph - Abu-Khzam, Faisal N. (2014)
This paper investigates the computational complexity of deciding whether the vertices of a graph can be partitioned into a disjoint union of cliques and a triangle-free subgraph. This problem is known to be NP-complete on arbitrary graphs. We show that this problem remains NP-complete even when restricted to planar graphs and perfect graphs.